Rough-surface SiC / C nano-composite fiber as well as preparation method and application thereof
By introducing zinc raw materials into SiC/C fibers and using electrospinning and high-temperature pyrolysis technology, the rough surface SiC/C nanocomposite fibers were prepared, which solved the problems of low dielectric constant and narrow effective absorption width of existing SiC fibers, and achieved excellent electromagnetic wave absorption performance.
Patent Information
- Application Number
- CN202411761796.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing SiC fibers have a low dielectric constant, narrow effective absorption width, concentrated in high-frequency regions, and lack effective broadband electromagnetic wave absorption materials.
By introducing zinc raw materials, electrospinning and high-temperature pyrolysis technology, rough surface SiC/C nanocomposite fibers are prepared, and an internal conductive network is established to improve electromagnetic wave absorption performance.
The electromagnetic wave absorption performance of SiC/C nanocomposite fibers is significantly improved, the effective absorption width is widened, and the real and imaginary parts of the dielectric constant are improved.
Smart Images

Figure CN119615416A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of electromagnetic wave absorbing materials, and in particular relates to a rough-surfaced SiC / C nanocomposite fiber and a preparation method and application thereof. Background Art
[0002] With the development of electromagnetic technology and electronic equipment, electromagnetic pollution is becoming more and more harmful to the health of life and precision electronic equipment, which makes electromagnetic wave absorption one of the hot research topics. Absorbing materials can effectively absorb or weaken the electromagnetic waves entering the interior, convert electromagnetic energy into internal energy or other forms of energy loss, and fundamentally avoid the harm of electromagnetic waves, which has attracted widespread attention from researchers. However, with the multiple demands of the application field, absorbing materials no longer simply emphasize strong attenuation, but also have higher requirements in terms of light weight and broadband, making the development of new absorber materials with excellent performance particularly important.
[0003] One-dimensional (1D) SiC materials have attracted much attention due to their high strength, high modulus, low density, excellent oxidation resistance, chemical stability, and good dielectric and electromagnetic properties. When used as an absorber material, compared with bulk and particles, the one-dimensional structure is conducive to building an internal conductive network to improve the conductive loss of the system. However, there are still some problems: first, pure SiC exhibits a low dielectric constant, and it is usually necessary to increase its dielectric constant through composite and structural design to optimize the electromagnetic wave impedance matching performance and loss capacity of the system; the effective absorption width of existing SiC fibers is narrow and concentrated in the high-frequency region. Therefore, there is an urgent need to develop efficient and broadband SiC fiber absorber materials. On the other hand, the introduction of metal elements (such as iron, cobalt, nickel, molybdenum, etc.) has been proven to be an effective method to improve the electromagnetic attenuation performance of SiC fibers. Zn is a low-temperature and easy-to-sublimate material. Based on this unique property, no research has yet applied it to the structural design and performance optimization of SiC fibers. Therefore, the introduction of zinc source into the SiC / C fiber system for rough structure design was explored to improve the electromagnetic wave absorption performance of SiC / C fibers, in the hope of preparing lightweight rough SiC / C nanofibers with excellent wave absorption properties. Summary of the invention
[0004] The present invention provides a rough-surfaced SiC / C nanocomposite fiber and a preparation method and application thereof for obtaining a nanofiber absorbing material with excellent absorbing performance. The preparation conditions are easy to achieve and the operation is simple. A simple electrospinning method and a high-temperature pyrolysis process are mainly adopted to obtain SiC / C nanofibers with a rough surface, good nanofiber morphology and excellent electromagnetic wave absorption performance.
[0005] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a rough-surfaced SiC / C nanocomposite fiber, comprising the following steps: Add polycarbosilane and zinc acetylacetonate into tetrahydrofuran to dissolve to obtain solution A, add polyvinyl pyrrolidone into dimethylformamide to obtain solution B, and continue stirring solution A and solution B until they are uniform; Adding a uniform solution A to a uniform solution B and mixing them evenly to obtain a spinning solution; According to the preset spinning conditions, the spinning solution is used to spin to obtain the precursor fiber; Performing pre-oxidation treatment on the precursor fiber to obtain pre-oxidized fiber; The pre-oxidized fibers were sintered in a N2 atmosphere and annealed to obtain SiC / C nanocomposite fibers with rough surfaces.
[0006] The mass volume ratio of the polycarbosilane, zinc acetylacetonate and tetrahydrofuran is (0.5-1.0) g: (0.1-0.2) g: (4-8) mL.
[0007] The mass volume ratio of the polyvinyl pyrrolidone and the nitrogen-nitrogen dimethylformamide is (0.5-1.0) g: (2-4) mL.
[0008] The preset spinning conditions include: The spinning speed is 0.1~0.4mm / min, the voltage is 15~20kv, the distance between the collecting drum and the spinneret is 15~20cm, and the rotation speed is 80~100r / min.
[0009] The pre-oxidation treatment is carried out at a temperature of 100-200° C. and for a time of 2-4 hours.
[0010] The stirring time for continuously stirring solution A and solution B until they are in a uniform state is 0.5 to 1.0 h. The solution A in a uniform state is added to the solution B in a uniform state and mixed evenly to obtain a spinning solution, specifically: The homogeneous solution A is added to the homogeneous solution B, and the mixture is magnetically stirred for 12 to 24 hours to obtain the spinning solution.
[0011] The sintering temperature is 1100-1200°C, and the time is 2-3h; the heating rate of the annealing treatment is 2-5°C / min, the temperature is 1200-1300°C, and the time is 2-4h. The present invention also provides a rough-surfaced SiC / C nanocomposite fiber prepared according to the above preparation method, wherein the average diameter of the SiC / C nanocomposite fiber is about 450 nm.
[0012] The rough surface SiC / C nanocomposite prepared by the invention is applied in the field of electromagnetic wave absorption.
[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention discloses a method for preparing a rough surface SiC / C nanocomposite fiber. The SiC / C nanofiber has a structural advantage that the one-dimensional structure is interlaced and built to facilitate the establishment of an internal conductive network, which is convenient for electrons to migrate inside the fiber and jump between fibers, and effectively enhances the conductivity loss. The introduction of Zn-containing raw materials effectively realizes the formation of a rough structure in the SiC / C fiber, and it has an obvious phase characteristic peak at 1200°C. The rough structure will effectively increase the interface area of the system, thereby significantly improving its electromagnetic wave absorption performance. The nanocomposite fiber prepared by this method has broad application prospects in electromagnetic wave absorption, using PCS dissolved in tetrahydrofuran as a silicon carbide source, adding PVP to adjust the viscosity of the spinning solution, and configuring the required spinning solution. It is worth noting that the addition of zinc acetylacetonate or zinc acetate has little effect on the viscosity of the spinning solution, and thus has little effect on the spinnability. The precursor nanofiber is prepared by an electrospinning process, and then air pre-oxidation and subsequent high-temperature sintering are performed to obtain a rough surface SiC / C composite nanofiber with excellent wave absorption performance.
[0014] Furthermore, the mass volume ratio of polycarbosilane: zinc acetylacetonate (zinc acetate): tetrahydrofuran is (0.5~1.0) g: (0.1~0.2) g: (4~8) mL, and the ratio is optimized, which not only ensures SiC / C as the matrix fiber, but also designs its structure by introducing zinc-containing raw materials. Because PCS is not easily soluble in other solvents, there should be a sufficient amount of tetrahydrofuran to ensure the full dissolution of PCS and the zinc-containing raw materials. Furthermore, the mass volume ratio of PVP:DMF is (0.5~1.0)g:(2-5)mL. By controlling the ratio of PVP and DMF, the dissolution efficiency of PVP is ensured, and the effect of solution viscosity on spinning performance is comprehensively considered to improve the stability of the spinning process.
[0015] Furthermore, PCS and PVP are dissolved in tetrahydrofuran and DMF respectively, so that PCS and PVP are fully dissolved, and they are evenly dispersed by stirring for a sufficient time to avoid agglomeration, which is conducive to the full mixing of the solution in the next step and ensures the quality of the spinning solution. Furthermore, since the solvents need to be mutually soluble and the solute needs to diffuse in the mixed solution, the mixed solution requires appropriate stirring time to form a uniform and stable spinning solution to avoid problems such as uneven spinning and blockage caused by uneven spinning solution.
[0016] Furthermore, sufficient voltage is required to ensure that there is sufficient electrostatic traction between the spinning needle and the collecting device to form nanofibers. Too low a voltage will result in insufficient traction and the fibers cannot be fully stretched. The spinning speed should not be too fast or too slow. If the spinning speed is too fast, the spinning solution cannot be fully stretched in time under the action of electrostatics, resulting in the fibers being too thick or uneven in shape. If the spinning speed is too slow, the spinning process becomes inefficient and may even cause blockage due to excessive accumulation of spinning solution at the needle. An appropriate spinning speed ensures that the evenly injected spinning solution can be fully stretched into fibers under the action of electrostatics. Both the collection distance and the drum speed need to be within an appropriate range to ensure that the spun fibers are collected as much as possible without changing their original shape. If the collection distance is too close, the fibers will stick together due to incomplete solidification. If the speed is too fast, the fibers will be deformed due to excessive mechanical force.
[0017] Furthermore, the conditions set for the pre-oxidation treatment can fully volatilize the solvent in the fiber and stabilize the fiber shape. Too high a temperature will cause the solvent in the fiber to evaporate quickly and produce shrinkage or deformation, while too low a temperature will reduce the volatilization efficiency of the solvent. Furthermore, N2 is a commonly used inert gas with stable chemical properties. Sintering the pre-oxidized fiber in a N2 atmosphere can ensure the purity of the fiber and prevent the fiber from being oxidized and ablated. For the fiber sintering system, the heating rate must be within a certain range. The heating rate is one of the factors that affect the fiber morphology. If the sintering temperature is too high or the temperature rises too quickly, the thermal stress inside the fiber will increase sharply, which may lead to the destruction of the fiber structure and the breakage of the fiber. PCS cannot be converted into SiC in time, affecting the performance of the fiber. A rough SiC / C nanocomposite fiber is a high-performance absorbing material. Through the design of the present invention, the rough SiC / C nanocomposite fiber can construct an internal conductive network, and the rough structure increases the interface area, thereby improving the real and imaginary parts of the dielectric constant, enhancing the reflection loss, and significantly improving the effective absorption width, thereby significantly improving the electromagnetic wave absorption performance of the rough SiC / C nanocomposite fiber.
[0018] In summary, the method of the present invention has a simple process, and the prepared composite nanofibers have a complete morphology, uniform diameter distribution, increased roughness, and exhibit excellent microwave absorbing performance.
[0019] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for use in the embodiment: Figure 1 This is a SEM image of SiC / C nanofibers prepared in Example 1 without the introduction of zinc-containing raw materials; Figure 2 This is the SEM image of the rough surface SiC / C nanofiber prepared in Example 2; Figure 3 XRD comparison diagram of SiC / C nanofibers prepared in Examples 1, 2 and 3 with and without the introduction of zinc-containing raw materials, wherein the sintering temperature is 1200°C, and 1 and 2 represent the addition amount of zinc acetylacetonate of 0.1g and 0.2g respectively; Figure 4 The three-dimensional reflection loss diagrams of SiC / C nanofibers prepared in Examples 1 and 2 with and without the introduction of zinc-containing raw materials as absorbing materials, wherein (a) is a three-dimensional reflection loss diagram without the introduction of zinc-containing raw materials, and (b) is a three-dimensional reflection loss diagram with the introduction of zinc-containing raw materials; Figure 5 The real part (a) and imaginary part (b) of the dielectric constant of SiC / C nanofibers prepared with or without the introduction of zinc-containing raw materials for Examples 1, 2 and 3, wherein 1 and 2 represent the addition amount of zinc acetylacetonate of 0.1 g and 0.2 g, respectively; Figure 6 The effective absorption width of the roughened SiC / C-1 prepared in Example 2 at different thicknesses. DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned herein can be combined with each other to form a new technical solution.
[0023] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.
[0024] In the present invention, unless otherwise specified, percentage (%) or part refers to the weight percentage or weight part relative to the composition.
[0025] In the present invention, unless otherwise specified, the components or preferred components involved can be combined with each other to form a new technical solution.
[0026] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "6-22" means that all real numbers between "6-22" have been listed in this document, and "6-22" is just an abbreviation of these numerical combinations.
[0027] The “range” disclosed in the present invention is in the form of a lower limit and an upper limit, which can be one or more lower limits, and one or more upper limits, respectively.
[0028] In the present invention, the term "and / or" used herein refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations.
[0029] In the present invention, unless otherwise specified, each reaction or operation step can be carried out sequentially or in accordance with the sequence. Preferably, the reaction method herein is carried out sequentially.
[0030] Unless otherwise specified, the professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any method or material similar or equivalent to the described content may also be applied to the present invention.
[0031] The present invention provides a rough surface SiC / C nanocomposite fiber and a preparation method and application thereof. Polycarbosilane (PCS) and zinc acetylacetonate are dissolved in tetrahydrofuran solvent in proportion, and PVP is dissolved in DMF solvent in proportion to prepare uniform solutions respectively; the two solutions are mixed and stirred for a sufficient time to make them uniform, and the obtained uniform solution is electrospun to obtain a SiC / C precursor fiber containing Zn with a specific composition; the precursor fiber is pyrolyzed at high temperature in an inert atmosphere to obtain the desired rough surface SiC / C nanofiber; the rough surface SiC / C nanofiber is mixed with paraffin in a certain proportion to prepare a dielectric sample, and its electromagnetic wave absorption performance is tested; the addition of zinc acetylacetonate not only effectively improves the structural stability of SiC / C, but also the rough surface structure design effectively broadens the effective absorption width of the composite fiber. The present invention uses zinc acetylacetonate as an additive for the first time, and prepares SiC / C nanofibers with rough surfaces and good electromagnetic wave absorption performance through electrospinning and high temperature pyrolysis.
[0032] The present invention provides a method for preparing a rough-surfaced SiC / C nanocomposite fiber, comprising the following steps: S1. Put polycarbosilane (PCS) and zinc acetylacetonate into a weighing bottle, and dissolve them in tetrahydrofuran in a certain proportion to obtain solution A; put polyvinylpyrrolidone (PVP) into a weighing bottle, and add dimethylformamide (DMF) to obtain solution B. Stir the obtained solutions A and B in a magnetic stirrer for 0.5-1.0h respectively until they are in a uniform state; Among them, the mass volume ratio of polycarbosilane: zinc acetylacetonate: tetrahydrofuran is (0.5~1.0) g: (0.1~0.2) g: (4~8) mL; the mass volume ratio of PVP: DMF is (0.5~1.0) g: (2~4) mL. S2, slowly adding the uniform solution A obtained in step S1 to the uniform solution B under magnetic stirring, and then stirring for 12 to 24 hours to fully mix the two solutions to obtain a stable spinning solution; S3, controlling the voltage to 15-20 kV, the distance between the collecting drum and the spinneret to 15-20 cm, the rotation speed to 80-100 r / min, spinning with the spinning solution at a constant speed of 0.1-0.4 mm / min to obtain a precursor fiber; Among them, the needle is a 23-gauge needle with an inner diameter of 0.3 mm.
[0033] S4, collecting the precursor fiber obtained in step S3 on aluminum foil, and pre-oxidizing it in a blast drying oven at a temperature of 100-200° C. for 2-4 hours to obtain pre-oxidized fiber; S5. Sinter the pre-oxidized fiber obtained in step S4 at 1100-1200° C. for 2-3 h in a N2 atmosphere, heat it to 1200-1300° C. at a rate of 2-5° C. / min, and anneal it for 2-4 h to obtain a SiC / C nanocomposite fiber with a rough surface. The rough surface SiC / C nanocomposite fiber prepared by the present invention not only has the excellent performance of silicon carbide in resisting harsh environments, but also has the morphological characteristics of nanofibers such as high specific surface area and high aspect ratio. The introduction of zinc raw materials further realizes the formation of a rough structure.
[0034] Pure silicon carbide fiber has relatively low real and imaginary values of the dielectric constant, mainly dominated by dielectric loss, with a narrow effective absorption width and low loss capacity. The introduction of zinc acetylacetonate generates SiC / C nanofibers with a rough surface structure, which significantly improves the effective absorption width and optimal reflection loss.
[0035] In summary, the rough surface SiC / C nanocomposite fibers have a simple preparation method and expected microwave absorption performance, and have certain application prospects.
[0036] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can usually be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0037] Example 1 Weigh 0.5 g of polycarbosilane and 0.1 g of zinc acetylacetonate, and then dissolve them in 7 mL of tetrahydrofuran. Stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution A. Weigh 0.5 g of PVP and dissolve it in 4 mL of DMF. Stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution B. Under the action of magnetic stirring, solution A was slowly added into solution B, and magnetic stirring was performed for 12 h until a uniform and stable spinning solution C was obtained; A No. 23 needle with an inner diameter of 0.3 mm was selected, and spinning was performed with spinning solution C at a constant speed of 0.2 mm / min at a voltage of 16 kV, a collecting drum 15 cm away from the spinning needle, and a rotation speed of 100 r / min to obtain a precursor fiber; The obtained precursor fibers were collected and pre-oxidized in a 200°C forced air drying oven for 2 h to obtain pre-oxidized fibers. The pre-oxidized fibers were then sintered at 1100°C for 3 h in a N2 atmosphere, heated at 2.5°C / min, and annealed at 1200°C for 2 h to obtain SiC / C nanofibers.
[0038] The spinning is uniform and continuous, maintaining the one-dimensional morphology of the nanofibers. Since no Zn salt is introduced, the SiC / C fibers have no rough structure. Example 2 Weigh 0.5 g of polycarbosilane and 0.15 g of zinc acetylacetonate, and then dissolve them in 7 mL of tetrahydrofuran. Stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution A. Weigh 0.5 g of PVP and dissolve it in 4 mL of DMF. Stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution B. Under the action of magnetic stirring, solution A was slowly added into solution B, and magnetic stirring was performed for 12 h until a uniform and stable spinning solution C was obtained; A No. 23 needle with an inner diameter of 0.3 mm was selected, and spinning was performed with spinning solution C at a constant speed of 0.2 mm / min at a voltage of 16 kV, a collecting drum 15 cm away from the spinning needle, and a rotation speed of 100 r / min to obtain a precursor fiber; The obtained precursor fibers were collected and pre-oxidized in a 150°C forced air drying oven for 3 h to obtain pre-oxidized fibers. The pre-oxidized fibers were then sintered at 1100°C for 3 h in a N2 atmosphere, heated at 2.5°C / min, and annealed at 1200°C for 2 h to obtain SiC / C nanofibers with rough surfaces.
[0039] Due to the unchanged parameters in spinning, the diameter of the fiber remains almost unchanged, and the fiber remains long and continuous as a whole. The introduction of rough structure improves both the real and imaginary parts of the dielectric constant of the system.
[0040] Example 3 Weigh 0.8 g of polycarbosilane (PCS) and 0.2 g of zinc acetylacetonate, and then dissolve them in 7 ml of tetrahydrofuran (THF). Stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution A. Weigh 0.5 g of polyvinylpyrrolidone (PVP) and dissolve it in 4 mL of DMF. Stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution B. Under magnetic stirring, solution A was slowly added into solution B, and magnetic stirring was performed for 12 h until a uniform and stable spinning solution C was obtained; A No. 23 needle with an inner diameter of 0.3 mm was selected, and spinning was performed with spinning solution C at a constant speed of 0.42 mm / min at a voltage of 15 kV, a collection drum 16 cm away from the spinneret, and a rotation speed of 100 r / min to obtain a precursor fiber; The obtained precursor fibers were collected and pre-oxidized in a 200°C forced air drying oven for 2 h to obtain pre-oxidized fibers. The pre-oxidized fibers were then sintered at 1200°C for 3 h in a N2 atmosphere, heated at 5°C / min, and annealed at 1300°C for 2 h to obtain rough SiC / C nanofibers.
[0041] It can be clearly seen that the viscosity of the solution increases due to the increase in the amount of zinc acetylacetonate added, making spinning difficult. Example 4 Weigh 1 g of polycarbosilane and 0.18 g of zinc acetylacetonate, then dissolve them in 8 mL of tetrahydrofuran, and stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution A; Weigh 1 g of PVP and dissolve it in 4 mL of DMF. Stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution B. Under the action of magnetic stirring, solution A was slowly added into solution B, and magnetic stirring was performed for 12 h until a uniform and stable spinning solution C was obtained; A No. 23 needle with an inner diameter of 0.3 mm was selected, and spinning was performed with spinning solution C at a constant speed of 0.2 mm / min at a voltage of 20 kV, a collecting drum 15 cm away from the spinning needle, and a rotation speed of 100 r / min to obtain a precursor fiber; The obtained precursor fibers were collected and pre-oxidized in a 200°C forced air drying oven for 2 h to obtain pre-oxidized fibers. The pre-oxidized fibers were then sintered at 1100°C for 2 h in a N2 atmosphere, heated at 5°C / min, and annealed at 1300°C for 2 h to obtain SiC / C nanofibers with rough surfaces.
[0042] Due to the excessive sintering temperature, the fiber becomes more brittle and breaks.
[0043] Example 5 Weigh 0.5 g of polycarbosilane and 0.1 g of zinc acetylacetonate, and then dissolve them in 7 mL of tetrahydrofuran. Stir the solution under magnetic stirring for 0.5 h to obtain a uniform solution A. Meanwhile, 0.8 g of PVP was weighed and dissolved in 3 mL of DMF, and the solution was stirred under magnetic stirring for 0.5 h to obtain a uniform solution B; Under the action of magnetic stirring, solution A was slowly added into solution B, and magnetic stirring was performed for 12 h until a uniform and stable spinning solution C was obtained; Then, a No. 23 needle with an inner diameter of 0.3 mm was selected, and spinning was performed with spinning solution C at a constant speed of 0.2 mm / min at a voltage of 20 kV, a collecting drum 15 cm away from the spinning needle, and a rotation speed of 100 r / min to obtain a precursor fiber; The obtained precursor fibers were collected and pre-oxidized in a 100°C forced air drying oven for 4 h to obtain pre-oxidized fibers. The pre-oxidized fibers were then sintered at 1200°C for 2 h in a N2 atmosphere, heated at 2°C / min, and annealed at 1300°C for 4 h to obtain SiC / C nanofibers with rough surfaces.
[0044] See also Figure 1 It can be seen that the nanofibers maintain a one-dimensional morphology, and due to the lack of the introduction of Zn salt, no rough structure appears in the SiC / C nanofibers.
[0045] See also Figure 2 , it can be seen that the SiC / C nanofibers generated after adding zinc acetylacetonate not only maintain the 1D structure, but also have a rough surface structure.
[0046] See also Figure 3 It can be seen that after adding zinc acetylacetonate, amorphous SiC is generated, the diffraction peak of SiC disappears, and no obvious diffraction peak of Zn appears.
[0047] See also Figure 4 , it can be seen that the optimal reflection loss value of the nanofibers generated by adding zinc acetylacetonate is significantly improved.
[0048] See also Figure 5It can be seen that the real and imaginary parts of the dielectric constant of the rough surface SiC / C nanocomposite fibers generated by adding zinc acetylacetonate are significantly improved.
[0049] See also Figure 6 It can be seen that the effective absorption width of the nanofibers with the addition of zinc acetylacetonate is significantly improved, and full coverage of the Ku and X bands and most of the C band can be achieved at different thicknesses.
[0050] In summary, the present invention provides a rough surface SiC / C nanocomposite fiber and its preparation method and application. PCS is used as the silicon carbide source, and zinc acetylacetonate is added. Not only does it maintain the 1D fiber structure, but it also generates a rough surface SiC / C nanocomposite fiber, improves the real and imaginary values of the dielectric constant, and introduces multiple loss mechanisms to achieve optimal impedance matching and electromagnetic loss. The use of electrospinning equipment directly prepares one-dimensional SiC / C nanocomposite fibers, combining the advantages of materials and nanostructures. A microwave absorbing material with good performance is prepared by a simple process.
[0051] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article.
[0052] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art can still modify or make equivalent substitutions to the specific implementations of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the scope of protection of the claims of the present invention to be approved.
Claims
1. A method for preparing a rough-surfaced SiC / C nanocomposite fiber, characterized in that: The following steps are involved: Add polycarbosilane and zinc acetylacetonate into tetrahydrofuran to dissolve to obtain solution A, add polyvinyl pyrrolidone into dimethylformamide to obtain solution B, and continue stirring solution A and solution B until they are uniform; Adding a uniform solution A to a uniform solution B and mixing them evenly to obtain a spinning solution; According to the preset spinning conditions, the spinning solution is used to spin to obtain the precursor fiber; Performing pre-oxidation treatment on the precursor fiber to obtain pre-oxidized fiber; The pre-oxidized fibers were sintered in a N2 atmosphere and annealed to obtain SiC / C nanocomposite fibers with rough surfaces.
2. The method for preparing a rough-surfaced SiC / C nanocomposite fiber according to claim 1, characterized in that: The mass volume ratio of the polycarbosilane, zinc acetylacetonate and tetrahydrofuran is (0.5-1.0) g: (0.1-0.2) g: (4-8) mL.
3. The method for preparing a rough-surfaced SiC / C nanocomposite fiber according to claim 1, characterized in that: The mass volume ratio of the polyvinyl pyrrolidone and the nitrogen-nitrogen dimethylformamide is (0.5-1.0) g: (2-4) mL.
4. The method for preparing a rough-surfaced SiC / C nanocomposite fiber according to claim 1, characterized in that: The preset spinning conditions include: The spinning speed is 0.1~0.4mm / min, the voltage is 15~20kv, the distance between the collecting drum and the spinneret is 15~20cm, and the rotation speed is 80~100r / min.
5. The method for preparing a rough-surfaced SiC / C nanocomposite fiber according to claim 1, characterized in that: The pre-oxidation treatment is carried out at a temperature of 100-200° C. and for a time of 2-4 hours.
6. The method for preparing a rough-surfaced SiC / C nanocomposite fiber according to claim 1, characterized in that: The stirring time for continuously stirring solution A and solution B until they are in a uniform state is 0.5 to 1.0 h.
7. The method for preparing a rough-surfaced SiC / C nanocomposite fiber according to claim 1, characterized in that: The solution A in a uniform state is added to the solution B in a uniform state and mixed evenly to obtain a spinning solution, specifically: The homogeneous solution A is added to the homogeneous solution B, and the mixture is magnetically stirred for 12 to 24 hours to obtain the spinning solution.
8. The method for preparing a rough-surfaced SiC / C nanocomposite fiber according to claim 1, characterized in that: The sintering temperature is 1100-1200°C, and the time is 2-3h; the heating rate of the annealing treatment is 2-5°C / min, the temperature is 1200-1300°C, and the time is 2-4h.
9. A SiC / C nanocomposite fiber with rough surface obtained by the preparation method according to any one of claims 1 to 8.
10. Application of the rough surface SiC / C nanocomposite according to claim 9 in the field of electromagnetic wave absorption.
Citation Information
Patent Citations
Preparation method for oxide ceramic coating on surface of wave-absorbing material powder
CN106399968A
Preparation method of flexible hydrophobic silicon carbide nanofiber cloth with electromagnetic wave absorption effect
CN106757529A
Flexible SiC / C nano-composite fiber as well as preparation method and application thereof
CN113737314A
Three-axis spinning super-elastic high-temperature-resistant composite carbon nanofiber aerogel and preparation method thereof
CN118685891A